举一反三
- 设\( A \)为\( n \) 阶方阵, \( B \)是\( A \)经过若干次初等变换后得到的矩阵,则( ) A: \( \left| A \right| = \left| B \right| \) B: \( \left| A \right| \ne \left| B \right| \) C: 若\( \left| A \right| = 0 \) ,则必有 \( \left| B \right| = 0 \) D: 若\( \left| A \right| > 0 \),则一定有\( \left| B \right| > 0 \)
- 设`\n`阶方阵`\A`经过初等变换后得方阵`\B`,则 ( ) A: \[\left| {\rm{A}} \right| = \left| {\rm{B}} \right|\] B: \[\left| A \right| \ne \left| B \right|\] C: \[\left| A \right|\left| B \right| \ge {\rm{0}}\] D: 若`\| A| = 0`,则`\| B| = 0`
- 设\( n \) 阶方阵 \( A,B \)相似,则 \( \left| A \right| = \left| B \right| \).
- 设\( A \) 为 \( n \)阶方阵,则 \( \left| {5A} \right| = 5\left| A \right| \).
- 设\( A,B \)均为\( n \)阶方阵,则必有( ) A: \( \left| {A + B} \right| = \left| A \right| + \left| B \right| \) B: \( AB = BA \) C: \( \left| {AB} \right| = \left| {BA} \right| \) D: \( {\left( {A + B} \right)^{ - 1}} = {A^{ - 1}} + {B^{ - 1}} \)
内容
- 0
设 \( A \), \( B \)为 \( n \)阶方阵,已知\( A \ne B \) ,则 \( \left| A \right| \ne \left| B \right| \).
- 1
设\(A\)为\(n\)阶方阵,\(\left| A \right| = 2 \),则\(\left| {\left| A \right|{A^T}} \right|=\) A: \({2^{n + 1}} \) B: \({2^{n }}\) C: \({2^{n - 1}}\) D: \(2\)
- 2
\(A,B\)均为\(n\)阶方阵,且\(A\)与\(B\)合同,\( R\left( A \right) = 4 \),则\( R\left( B \right) = \) ______
- 3
设\( A,\;B \) 均为\( n \) 阶方阵,则必有( ). A: \( {(A + B)^2} = {A^2} + 2AB + {B^2} \) B: \( \left| {A + B} \right| = \left| A \right| + \left| B \right| \) C: \( \left| {AB} \right| = \left| A \right|{\kern 1pt} \left| B \right| \) D: \( {\left( {AB} \right)^{\rm T}} = {A^{\rm T}}{B^{\rm T}} \)
- 4
设 \( A \)为 \( n \)阶方阵,且\( \left| A \right| = a \ne 0 \) ,则 \( \left| { { A^ * }} \right| = \)( ) A: \( a \) B: \( {1 \over a} \) C: \( {a^{n - 1}} \) D: \( {a^n} \)